2007
DOI: 10.1159/000108590
|View full text |Cite
|
Sign up to set email alerts
|

Dual Action of Nitric Oxide in the Pathogenesis of Ischemia/Reperfusion-Induced Mucosal Injury in Mouse Stomach

Abstract: Aim: We investigated the roles of NO/NOS isoforms in the pathogenesis of ischemia/reperfusion (I/R)-induced gastric injury in mouse stomachs. Methods: Under urethane anesthesia, the celiac artery was clamped, and then reperfusion was established 30 min later by removal of the clamp. After a 60-min reperfusion, the stomach was examined for macroscopic lesions. Results: Following I/R, hemorrhagic lesions were generated in the mucosa, although ischemia alone caused no visible damage. Prior administration of L-NAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 61 publications
8
23
1
1
Order By: Relevance
“…MPO activity was a marker to assay neutrophil infiltrations (Tiidus et al, 2005). In the present study, we observed a significant increase in MPO activity in the stomach after I/R, which was in agreement with previous research (Gou et al, 2011;Kobata et al, 2007), confirming the infiltration and activation of neutrophils in the gastric mucosa during I/R. However, the increased MPO activity induced by I/R was significantly inhibited by prior administration of rutin.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…MPO activity was a marker to assay neutrophil infiltrations (Tiidus et al, 2005). In the present study, we observed a significant increase in MPO activity in the stomach after I/R, which was in agreement with previous research (Gou et al, 2011;Kobata et al, 2007), confirming the infiltration and activation of neutrophils in the gastric mucosa during I/R. However, the increased MPO activity induced by I/R was significantly inhibited by prior administration of rutin.…”
Section: Discussionsupporting
confidence: 93%
“…Gastric I/R leads to tissue injury in gastric mucosa (Gou et al, 2011;Kobata et al, 2007). This study indicated a significant increase of lipid peroxidation and MPO activity, which were accompanied by alterations of cNOS and iNOS activities in the gastric mucosa induced by I/R.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It has been shown that mRNA and protein expression of iNOS is upregulated following gastric I/R injury in mice and rats (Kobata et al, 2007;Yi et al, 2012). Consistent with these findings, the present study demonstrated that iNOS protein expression drastically increased after I/R injury in the rat stomach.…”
Section: Discussionmentioning
confidence: 99%